Improving Students’ Vocabulary Achievement by Using Twitter and Instagram Multimedia - Sarma Sirait; Saidatul Hanim (Journal of Classroom Action Research, 2022)
This study attempts to improve students’ achievement in vocabulary by using Twitter and Instagram multimedia. This study was conducted by using classroom action research. The subject of the research was class VIII-2 SMP FREE METHODIST 2 Medan which consisted of 40 students. The research was conducted in two cycles, cycle I of four meeting and cycle II consisted of two meetings. The instruments for collecting data were quantitative data namely vocabulary test and qualitative data namely, observation sheet and questionnaire. .Based on quantitative data, in vocabulary test, students score kept improving in every test of vocabulary. The finding of this is Twitter and Instagram multimedia can improve the students’ vocabulary achievement. It can be prove from the calculation of test in both of cycles. The mean of pre test is 59. The students who got higher than 75 is 10%. The mean of post test cycle I is 75,75 and students who got higher than 75 is 26 students 65%. Te post test average on post test is 89,5, all of them 100% got higher than standard minimum. There is an improvement of the application of twitter and instagram multimedia to teach vocabulary in eight grade of SMP FREE METHODIST 2 Medan. Based on observation sheet and questionnaire sheet it was found that the students were active and enthusiastic in learning vocabulary by using twitter and instagram multmedia. The result of the research showed that twitter and instagram multimedia significantly improved students. Keywords: Vocabulary Achievement, Twitter, Instagram